2019
DOI: 10.1051/0004-6361/201935154
|View full text |Cite
|
Sign up to set email alerts
|

The Fornax 3D project: Thick disks in a cluster environment

Abstract: We used deep MUSE observations to perform a stellar-kinematic and population analysis of FCC 153 and FCC 177, two edge-on S0 galaxies in the Fornax cluster. The geometrical definition of the different structural components of these two galaxies allows us to describe the nature of their thick disks. These are both old, relatively metal poor and [Mg/Fe]-enhanced, and their star formation history (SFH) reveals a minor younger component whose chemical properties suggest its later accretion. Moreover, the outer reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 86 publications
3
18
0
Order By: Relevance
“…In Fahrion et al (2019b), we argued that the old age and high metallicity of the NSC in FCC 47 indicates an efficient formation at early times. Similar arguments were made in the detailed analysis of FCC 170 by Pinna et al (2019a) using the same F3D MUSE data which showed that FCC 170 assembled very rapidly and efficiently at early times (see also Poci et al 2021). Their SFH of the central region of FCC 170 is similar to the one presented here.…”
Section: Most Massive Galaxiessupporting
confidence: 86%
See 1 more Smart Citation
“…In Fahrion et al (2019b), we argued that the old age and high metallicity of the NSC in FCC 47 indicates an efficient formation at early times. Similar arguments were made in the detailed analysis of FCC 170 by Pinna et al (2019a) using the same F3D MUSE data which showed that FCC 170 assembled very rapidly and efficiently at early times (see also Poci et al 2021). Their SFH of the central region of FCC 170 is similar to the one presented here.…”
Section: Most Massive Galaxiessupporting
confidence: 86%
“…FCC 170 is an edge-on S0 galaxy with multiple structural components including a thin disk, thick disk, and a X-shaped bulge component (see e.g. Pinna et al 2019a;Poci et al 2021). Modelling this galaxy with imfit is challenging.…”
Section: Appendix B: Exemplary Binned Metallicity Mapsmentioning
confidence: 99%
“…Williams et al (2011) suggested that this galaxy may have a small classical bulge, which would make it different from M 31 with its sizeable classical bulge. Pinna et al (2019b) studied another galaxy with a B/P bulge, FCC 177. However, this one does not have obvious signs of the B/P bulge in metallicity and certainly not in [Mg/Fe].…”
Section: Comparison With Other Galaxiesmentioning
confidence: 99%
“…Nevertheless, the presence of different structures is expected to modify the orbit of stars and leave distinct. For example, features such as a double thin-thick disc structure (Burstein 1979;Tsikoudi 1979), warps (Reshetnikov & Combes 1998;Ann & Park 2006;Reshetnikov et al 2016), rings (Few & Madore 1986), single and double bars (Shlosman, Frank & Begelman 1989;de Lorenzo-Cáceres et al 2019), disc breaks (van der Kruit 1979; Pohlen et al 2004;Martín-Navarro et al 2012), and spiral arms (Danver 1942;Bittner et al 2020a) leave different imprints in the kinematics and stellar populations properties that help us disentangle different evolutionary paths (Pinna et al 2019;Gadotti et al 2020;Rosado-Belza et al 2020;Bittner et al 2020b) This type of analysis is extremely useful in the Milky Way, where we have access to the full six-dimensional (6D) information E-mail: dwalo@iac.es, danielwalo@hotmail.com (positions and velocities), chemical abundances, and ages of the stars. Thanks to missions like GAIA (Gaia Collaboration et al 2016) and APOGEE (Majewski et al 2017), we now have access to the properties of millions of stars in a large region of our Galaxy which allows us to study the spatial variations of the stellar kinematics beyond the solar neighbourhood.…”
Section: Introductionmentioning
confidence: 99%